2020
DOI: 10.1007/s11661-020-06017-3
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Characteristics and Impact Fracture Behaviors of a Novel High-Strength Low-Carbon Bainitic Steel with Different Reheated Coarse-Grained Heat-Affected Zones

Abstract: To obtain the correlation of microstructural characteristics and toughness in a novel high-strength low-carbon bainitic structural steel with medium and heavy plate after multipass welding, a welding thermal simulation experiment was conducted to simulate different subregions in the reheated coarse-grained heat-affected zones (CGHAZ). The microstructure evolution was then analyzed and factors that influence the fracture behavior were studied. The results show that the brittle zone appeared in subcritical rehea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…[ 20 ] As mentioned earlier, large blocky M/A constituents were the source of cracks initiation. [ 21 ] Generally, stress concentration is localized at the interface between the steel substrate and coarse M/A constituents, which is difficult to relieve. Cracks were preferred to nucleate and propagate at such a weak interface, and finally deteriorated the impact toughness.…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 ] As mentioned earlier, large blocky M/A constituents were the source of cracks initiation. [ 21 ] Generally, stress concentration is localized at the interface between the steel substrate and coarse M/A constituents, which is difficult to relieve. Cracks were preferred to nucleate and propagate at such a weak interface, and finally deteriorated the impact toughness.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also reported that the loss in toughness is not just due to the presence of RA phase, but is related to the distribution and morphology of the RA constituent, and the matrix microstructure. Cui et al [ 32 ] reported that block residual austenite significantly deteriorates impact toughness of super-critical reheated coarse grain heat affected zone (SC CGHAZ).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has showed that the inter-critically reheated coarse-grained heat-affected zone (ICR CGHAZ) is the location with the poorest fracture toughness in the multi-pass welding heat-affected zone [ 5 , 6 ]. Therefore, methods to optimize mechanical properties, especially toughness, have become popular in the research on high-strength and ultra-high-strength steel [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%